Respon Pertumbuhan dan Produksi Tanaman Pakcoy (Brasicca rapa L.) Terhadap Kombinasi Pemberian POC Daun Gamal dan 50% NPK - Amyu, Wina Dwi; Ibnusina, Fedri; Darnetti, (Jurnal Pertanian, 2025)
The pakcoy plant (Brassica rapa L) is an agricultural crop that is relatively short-lived and can be harvested in a short time. The high use of chemical fertilizers that have the potential to damage the soil is the main problem underlying this research because of this, it is important to find fertilizers that are not only effective but also environmentally friendly. This study aims to determine the effect of the combination of gamal leaf liquid organic fertilizer and 50% NPK fertilizer on the growth and production of pakcoy (Brassica rapa L) plants. The method used was Group Random Design with 3 treatments of 100% inorganic fertilizer, 150 ml of POC + 50% NPK gamal leaves, 170ml POC of gamal leaves + 50% NPK, repeated for 9 replications. Observations observed included leaf count, leaf width, leaf length, wet weight, crown weight, root weight, and root length. Based on the results of the study, significant results were obtained in the observation of leaf length (cm) and root length (cm), while insignificant results were obtained in the observation of the number of leaves (strands), leaf width (cm), fresh weight (g), crown weight (g), and root weight (g). This study showed that the application of gamal leaves and NPK liquid organic fertilizer in combination gave results that were not significantly different from the application of pure NPK fertilizer in the observation of leaf count, leaf width, fresh weight, crown weight, and root weight, but showed significant differences in leaf length and width. The results of this research can be used as a reference to improve soil conditions and support sustainable agriculture that is environmentally friendly. Keywords: Nutrient, critical land, sustainable agriculture, environmentally friendly